Model strateškega odločanja distribucije orodij z uporabo pravil mehke logike - Vrečer, Gorazd (Strojniški vestnik, 2000)
This paper concerns the working out of a fuzzy algorithm model to simulate the dynamic system of tool distribution. A model of tool motion in the production process and in the store of a medium-size company is made. In a company, the production flexibility depends to a large extent on the high-quality manufacturing and the flow and the strategic distribution of tools, which must always be available in time and in sufficient quantities. Tool flow is dynamical and can be monitored according to fuzzy algorithm principles by means of feedback signals with which the desired and obtained values are compared and the flow controlled. This paper shows the model with which we presented the time delays occuring during the tool distribution. The presented real tool distribution monitoring system of a company comprises the flow of materials, informations and production means. The system features the interconnections between the individual units of the company, involved in the information flows with which the flexibility of the system was increased.
Keywords: pretok orodij; načrtovanje; modeli; logika mehka; mehka logika; pretok; orodja